Impact of Genetic and Epigenetic Variations Within the FADS Cluster on the Composition and Metabolism of Polyunsaturated Fatty Acids in Prostate Cancer. Issue 13 (16th May 2016) - Cui, Tao; Hester, Austin G.; Seeds, Michael C.; Rahbar, Elaheh; Howard, Timothy D.; Sergeant, Susan; Chilton, Floyd H.
Abstract : BACKGROUND: In vitro and experimental animal studies have demonstrated that high levels of omega‐6 (n‐6) polyunsaturated fatty acids (PUFAs) and high ratios of n‐6 to omega‐3 (n‐3) PUFAs are strongly associated with the development and progression of prostate cancer (PCA). However, epidemiological studies in humans have demonstrated inconsistent findings linking dietary PUFAs and PCA risk. We hypothesize that genetic and epigenetic variations within the fatty acid desaturase ( FADS ) gene cluster produce gene–diet interactions that may explain these disparate findings. This study tested the relationship of the genotype of a single nucleotide polymorphism, rs174537, and the methylation status of a CpG site, cg27386326, with PUFA composition, and markers of PUFA biosynthesis in PCA tissue. METHODS: Sixty PCA specimens from patients undergoing radical prostatectomy were genotyped, pyrosequenced and quantitated for fatty acids (FAs). RESULTS: Long‐chain (LC)‐PUFAs, such as arachidonic acid (ARA), were abundant in these specimens, with ARA accounting for 15.8% of total FAs. In addition, there was a positive association of the G allele at rs174537 with concentrations of ARA and adrenic acid and ratios of products to precursors within the n‐6 PUFA pathway such that specimens from homozygous G individuals exhibited increasingly higher values as compared to specimens from heterozygous individuals and homozygous T individuals. Finally, the methylation status of cg27386326 was inversely correlated with tissue concentrations of LC‐PUFAs and markers of LC‐PUFA biosynthesis. CONCLUSIONS: These data reveal that genetic and epigenetic variations within the FADS cluster are highly associated with LC‐PUFA concentrations and LC‐PUFA biosynthetic capacity in PCA tissue. They also raise the potential that gene–PUFA interactions play an important role in PCA risk and severity. Prostate 76:1182–1191, 2016 . © 2016 The Authors. The Prostate published by Wiley Periodicals, Inc.